An efficient bilateral remote user authentication scheme with smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon (2006)
In this paper, we propose an efficient bilateral remote user authentication scheme with smart cards. Our scheme ensures both-way authentication, so that any attempt of the adversary to affect the secure communications between the authentication server and the user could not be successful. We also present a brief analysis of our proposed scheme and show that it is well-resistant against the known attacks in remote user authentication process.